Prognostic factors related to delayed healing of venous leg ulcer treated with compression therapy - Vesna Karanikolic; Aleksandar Karanikolic; Dejan Petrovic; Milenko Stanojevic (Wolters Kluwer Medknow Publications, 2015)
Background: The basic goal of this research was to determine and evaluate the prognostic factors related to the delay of venous ulcer healing in patients treated with multilayer compression bandage. Methods: The research involved a group of 100 patients of both sexes with venous ulcerations of the lower extremities. Patients were monitored for 24 weeks from the very beginning of the treatment. Ulcerations were treated with the use of multiple layer compression bandages. Results: Of the total number of tested patients, 58 (58%) were females and 42 (42%) were males. The average age of patients was 62.7 ± 6.53 years, where the male population was older. During the 24-week monitoring period, 25 patients (25%) did not heal completely. Lipodermosclerosis has a significant positive prognostic significance in healing chronic venous ulcers (p < 0.05). The infection proved to be the most important prognostic factor in the delay of ulcer healing (p < 0.01). The number and surface of ulcerative changes show a significant positive correlation with delay of venous ulcer healing (p < 0.001). Conclusion: The results of this study show a significant positive correlation between the number and surface of ulcerative changes and the delay of venous ulcer healing. Further trials are necessary to identify the best treatment options, especially for nonhealing ulcers.